DEVELOPING A DIGITAL LEARNING MANAGEMENT MODEL BASED ON BUDDHIST PRINCIPLES FOR SMALL SCHOOLS UNDER NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 3 - Chomthong, Chuthamas; Weeraponkan, Boonlert; Somkhaoyai, Teeraphong (Journal of MCU Nakhondhat, 2025)
This research aimed to: 1) Study the current conditions, problems, and needs regarding learning management in small schools; 2) Develop a learning management model based on digital technology integrated with Buddhist principles; 3) Implement the developed model; and 4) Evaluate the appropriateness, feasibility, and usefulness of the model. A mixed-methods design was employed. The participants included 206 schools administrators and academic teachers, 15 key informants from in-depth interviews, 5 experts, 9 participants in an expert seminar, and 10 respondents for satisfaction assessment. Research instruments comprised questionnaires, interview guides, expert seminar forms, observation forms, model evaluation forms, and satisfaction surveys. Data were analyzed using percentage, mean, standard deviation, the Priority Needs Index (PNI), and descriptive analysis. The findings revealed that 1) The current state of learning management was at a moderate level, while the expected state was at the highest level. The greatest need was curriculum (PNI = 0.94), followed by instructional media (0.89) and instructional management (0.85). 2) The developed model consisted of principles, objectives, and implementation methods in four areas: curriculum, instructional management, instructional media, and assessment and evaluation, along with success factors. 3) Trial implementation showed significant improvement in knowledge scores (from 11.70 to 17.90), with lesson planning at a high level, and learning management, supervision, and monitoring at the highest level. 4) Overall evaluation indicated the highest levels of appropriateness, feasibility, and usefulness, and have a minimum point that can be used effectively.